Effects of Mental Training Through Imagery on the Competitive Anxiety of Adolescent Tennis Players Fasting During Ramadan: A Randomized, Controlled Experimental Study - Fekih, Sofien; Zguira, Mohamed Sami; Koubaa, Abdessalem; Bettaieb, Anouar; Hajji, Jamel; Bragazzi, Nicola Luigi; Jarraya, Mohamed (Frontiers in Nutrition, 2021)
Abstract: This study aimed to analyze the effects of mental training through imagery on the competitive anxiety of young tennis players fasting during Ramadan. This is an experimental study conducted with 38 male tennis players, randomly divided into two groups: experimental group (EG, n = 18), aged (16.9 ± 0.6 years) and control group (CG, n = 20) aged 16.7 ± 0.8 years. The study was designed as a randomized and controlled experimental study. Control group watched historical videos of the Olympics, while experimental group performed mental training. The competitive anxiety state assessment was taken four times. The first measurement was carried out, one week before Ramadan, the second measurement was carried out during the first week of this month, the third measurement was carried out at the end of the second week, and finally a fourth measurement was carried out during the fourth week of Ramadan. Our results revealed a significant interaction [Time x Groups] for all competitive anxiety subscales. Higher intensity and direction for the cognitive and somatic anxiety subscale during Ramadan compared to before-Ramadan for both groups at (P <0.001). Higher intensity and direction for the cognitive and somatic anxiety subscale during Ramadan compared to pre-Ramadan for both groups at (P <0.01). This increase in scores was greater for the control group than for the experimental group in the middle and end of Ramadan at (P <0.001). Finally for the self-confidence subscale score, results revealed that intensity and direction were lower during Ramadan compared to pre-Ramadan for the two groups at (P <0.01). The score for the intensity of self-confidence is higher for the experimental group compared to the control group at the end of Ramadan at (p <0.001). It was concluded that mental imagery training was effective in reducing anxiety (cognitive and somatic) and increasing self-confidence in the intensity dimension of young tennis players who fast during Ramadan.